Impacts of normative information on college students’ energy-saving intentions and behaviors in the dormitory - Ning Liu; Xi Luo; Xiaojun Liu; Menglin Xing (Energy and Built Environment)
College students’ energy-saving behaviors in dormitory buildings are crucial for reducing energy consumption on university campuses. An information framework aimed at normalization can do well in motivating individuals’ energy-saving behaviors. To assess the effectiveness of normative information intervention strategies in motivating college students to save energy, this study innovatively adopts a new method combining traditional influence path analysis and field experiment, which makes up for the shortcomings of the traditional single questionnaire survey method. First, this study introduced “normative information” and “personal norms” into the theory of planned behavior (TPB). The aim was to explore the mechanisms by which the provision of normative information affects college students’ energy-saving intentions through a questionnaire (352 questionnaires). Then, on this basis, a field experiment was conducted in 70 university dormitories with 313 students to further assess the effectiveness of four normative information intervention strategies in promoting energy-saving behaviors. The study results showed: 1) Attitude, perceived behavioral control, subjective norms, and personal norms were significantly correlated with energy-saving intentions. 2) Positive normative feedback and low-intensity normative feedback had significant positive effects on personal norms, which fully mediated the relationships between positive/low-intensity normative feedback and energy-saving intentions. 3) Positive low-intensity normative information achieved the best energy-saving effect (with an energy-saving ratio of 29.18%), followed by positive high-intensity normative information (24.97%) and negative low-intensity normative information (24.38%). The results can provide reference for reducing dormitory energy consumption.